Consideraciones de diseño y cálculo de las instalaciones hidráulicas en una red de distribución de agua potable (2016)
In this paper the basic conditions for the design and calculation of hydraulic facilities of a distribution network of drinking water for a building are presented . It has taken into account the current regulations in the country and in the city of Bogota , also, the fundamental concepts of hydraulics and experience of different authors.